A Multiple-Vortex Tornado in Southeastern Brazil - Nascimento, Ernani de Lima; Held, Gerhard [UNESP]; Gomes, Ana Maria [UNESP] (Amer Meteorological Soc, 2014)
During the late afternoon hours of 24 May 2005 a severe weather outbreak occurred in the state of San Paulo, southeastern Brazil. Severe thunderstorms were observed ahead of a surface cold front, including a (Southern Hemisphere) cyclonic left-moving supercell that produced a multiple-vortex tornado in the outskirts of the town of Indaiatuba, Brazil (23.1 degrees S, 47.2 degrees W). A documentation of the multivortex structure of the tornado and of the cloud-base features is performed using still images from a video that recorded the event. Characteristics of the tomadic thunderstorm and the synoptic-scale environment in which it developed are examined using Doppler radar data, geostationary satellite imagery, surface and upper-air observations, and data from the National Centers for Environmental Prediction's Climate Forecast System Reanalysis. The cloud base of the thunderstorm displayed morphological features associated with midlatitude tornadic supercells, including a low-level mesocyclone and a "clear slot"; however, the rear-flank downdraft did not obscure the view of the tornado from the western flank of the storm. The tornadic storm developed in a moist prefrontal environment with a low-level jet. Limited mesoscale observations hampered the quantitative analysis of the local thermodynamic forcing, but the available data suggest that the supercell developed under moderate conditional instability. Strong speed and directional vertical wind shear were observed, while the local boundary layer displayed very high relative humidity and low surface-based lifting condensation level.